Poor efficacy of preemptive amoxicillin clavulanate for preventing secondary infection from Bothrops snakebites in the Brazilian Amazon: A randomized controlled clinical trial. - Jacqueline A G Sachett; Iran Mendonça da Silva; Eliane Campos Alves; Sâmella S Oliveira; Vanderson S Sampaio; Fábio Francesconi do Vale; Gustavo Adolfo Sierra Romero; Marcelo Cordeiro Dos Santos; Hedylamar Oliveira Marques; Mônica Colombini; Ana Maria Moura da Silva; Fan Hui Wen; et al. (Public Library of Science (PLoS), 2017)
Secondary bacterial infections from snakebites contribute to the high complication rates that can lead to permanent function loss and disabilities. Although common in endemic areas, routine empirical prophylactic use of antibiotics aiming to prevent secondary infection lacks a clearly defined policy. The aim of this work was to estimate the efficacy of amoxicillin clavulanate for reducing the secondary infection incidence in patients bitten by Bothrops snakes, and, secondarily, identify risk factors for secondary infections from snakebites in the Western Brazilian Amazon.This was an open-label, two-arm individually randomized superiority trial to prevent secondary infection from Bothrops snakebites. The antibiotic chosen for this clinical trial was oral amoxicillin clavulanate per seven days compared to no intervention. A total of 345 patients were assessed for eligibility in the study period. From this total, 187 accomplished the inclusion criteria and were randomized, 93 in the interventional group and 94 in the untreated control group. All randomized participants completed the 7 days follow-up period. Enzyme immunoassay confirmed Bothrops envenoming diagnosis in all participants. Primary outcome was defined as secondary infection (abscess and/or cellulitis) until day 7 after admission. Secondary infection incidence until 7 days after admission was 35.5% in the intervention group and 44.1% in the control group [RR = 0.80 (95%CI = 0.56 to 1.15; p = 0.235)]. Survival analysis demonstrated that the time from patient admission to the onset of secondary infection was not different between amoxicillin clavulanate treated and control group (Log-rank = 2.23; p = 0.789).Secondary infections incidence in 7 days of follow-up was independently associated to fibrinogen >400 mg/dL [AOR = 4.78 (95%CI = 2.17 to 10.55; p<0.001)], alanine transaminase >44 IU/L [AOR = 2.52 (95%CI = 1.06 to 5.98; p = 0.037)], C-reactive protein >6.5 mg/L [AOR = 2.98 (95%CI = 1.40 to 6.35; p = 0.005)], moderate pain [AOR = 24.30 (95%CI = 4.69 to 125.84; p<0.001)] and moderate snakebites [AOR = 2.43 (95%CI = 1.07 to 5.50; p = 0.034)].Preemptive amoxicillin clavulanate was not effective for preventing secondary infections from Bothrops snakebites. Laboratorial markers, such as high fibrinogen, alanine transaminase and C-reactive protein levels, and severity clinical grading of snakebites, may help to accurately diagnose secondary infections.Brazilian Clinical Trials Registry (ReBec): RBR-3h33wy; UTN Number: U1111-1169-1005.